Publisher's Note: Branching fraction measurement of B+→ωℓ+ν decays - Lees, Jean-Pierre; Adametz, Aleksandra; Uwer, Ulrich (Physical review. D, Particles, fields, gravitation, and cosmology, 2013)
DOI:https://doi.org/10.1103/PhysRevD.87.099904 [Phys. Rev. D 87, 032004 (2013)]